Host Immune Responses Differ between M. africanum- and M. tuberculosis-Infected Patients following Standard Anti-tuberculosis Treatment. - Leopold D Tientcheu; Mariëlle C Haks; Schadrac C Agbla; Jayne S Sutherland; Ifedayo M Adetifa; Simon Donkor; Edwin Quinten; Mohammed Daramy; Martin Antonio; Beate Kampmann; Tom H M Ottenhoff; Hazel M Dockrell; et al. (Public Library of Science (PLoS), 2016)
Epidemiological differences exist between Mycobacterium africanum (Maf)- and Mycobacterium tuberculosis (Mtb)-infected patients, but to date, contributing host factors have not been characterised. We analysed clinical outcomes, as well as soluble markers and gene expression profiles in unstimulated, and ESAT6/CFP-10-, whole-Maf- and Mtb-stimulated blood samples of 26 Maf- and 49 Mtb-HIV-negative tuberculosis patients before, and after 2 and 6 months of anti-tuberculosis therapy. Before treatment, both groups had similar clinical parameters, but differed in few cytokines concentration and gene expression profiles. Following treatment the body mass index, skinfold thickness and chest X-ray scores showed greater improvement in the Mtb- compared to Maf-infected patients, after adjusting for age, sex and ethnicity (p = 0.02; 0.04 and 0.007, respectively). In addition, in unstimulated blood, IL-12p70, IL12A and TLR9 were significantly higher in Maf-infected patients, while IL-15, IL-8 and MIP-1α were higher in Mtb-infected patients. Overnight stimulation with ESAT-6/CFP-10 induced significantly higher levels of IFN-γ and TNF-α production, as well as gene expression of CCL4, IL1B and TLR4 in Mtb- compared to Maf-infected patients. Our study confirms differences in clinical features and immune genes expression and concentration of proteins associated with inflammatory processes between Mtb- and Maf-infected patients following anti-tuberculosis treatment These findings have public health implications for treatment regimens, and biomarkers for tuberculosis diagnosis and susceptibility.